Learning organization practices : a case study at Sarawak royal Malaysia police headquarters, Kuching - Mohd. Taufik Toh, b. Abdullah (2004)
The purpose of this research is to assess factors that could make RMP a learning organization. The population of this study consists of the Senior Police Officers at RMP Headquarters Sarawak.